2021
DOI: 10.3390/ph14090913
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of a New Olive Pomace Functional Ingredient

Abstract: Olive pomace, an olive oil processing byproduct, can be upcycled and meet the current demand for natural and sustainable food ingredients. In this work, a patented process was used to obtain a functional ingredient from different olive pomaces. The nutritional, chemical and antioxidant profiles, as well as the antimicrobial activity against S. aureus, E. coli and C. albicans, were investigated for the first time. The amount of phenolics ranged between 3.1 and 3.8 g gallic acid eq./100 g in all samples and flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 41 publications
3
25
0
1
Order By: Relevance
“…These results are in agreement with the previous statement that ethanol has an important role in the recovery of biomolecules with higher antioxidant capacities [36]. Several authors reported that OP-derived extracts have an interesting antioxidant capacity that may be related to the content of phenolic compounds [34,37,38]. For example, Ribeiro et al [34] evaluated the antioxidant capacity of OP extracts using three different methods (DPPH, ABTS, and ORAC), and their results showed high antioxidant activity for the methanolic extracts of OP.…”
Section: Extraction Yield Phenolic Composition and Cell-free Antioxid...supporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with the previous statement that ethanol has an important role in the recovery of biomolecules with higher antioxidant capacities [36]. Several authors reported that OP-derived extracts have an interesting antioxidant capacity that may be related to the content of phenolic compounds [34,37,38]. For example, Ribeiro et al [34] evaluated the antioxidant capacity of OP extracts using three different methods (DPPH, ABTS, and ORAC), and their results showed high antioxidant activity for the methanolic extracts of OP.…”
Section: Extraction Yield Phenolic Composition and Cell-free Antioxid...supporting
confidence: 93%
“…Ribeiro et al [34] reported TPC values above 20 mg GAE/g OP using methanol as a solvent. On the other hand, Nunes et al [37] quantified about 30 mg GAE/g OP using water as the extraction medium.…”
Section: Extraction Yield Phenolic Composition and Cell-free Antioxid...mentioning
confidence: 99%
See 1 more Smart Citation
“…TVC ( Figure 1 a) and yeast and mold counts ( Figure 1 b) were the highest in the uncoated cucumber samples followed by those coated with 2% chitosan only, whereas the lowest counts were seen in cucumber coated with functional materials (2% OCE and 2% OPE), suggesting the protective effects of these materials against spoilage microbes in cucumber samples. The reduction in TVC and mold and yeast counts in the coated cucumber with chitosan containing OCE and OPE is likely due to the presence of the phytochemicals with high antimicrobial activity of olive cake and orange peel extract as reported previously [ 22 , 30 ]. In addition, the coating material formed a protective layer on the surface of the cucumber samples, thereby reducing the microbial contamination and growth [ 9 ].…”
Section: Resultssupporting
confidence: 60%
“…The Gram-negative bacteria have rigid cell walls, the main component of which are lipopolysaccharides, making these bacteria more resistant to different antibacterial agents. In contrast, the Gram-positive bacteria cell walls are homogeneous and do not contain phospholipids [ 73 ]. It is reported that the plant extracts are hydrophobic in nature, while the Gram-negative bacteria outer membranes have some hydrophilic porins; hence, the diffusion of the plant extract compounds into the Gram-negative bacteria is hindered [ 74 ].…”
Section: Resultsmentioning
confidence: 99%